1983
DOI: 10.1021/j100237a017
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 9,10-anthraquinone-2-sulfonate in solution. 1. Intermediates and mechanism

Abstract: The photochemistry of aqueous 9,10-anthraquinone-2-sulfonate (AQS) was investigated by using four different approaches: (1) laser photolysis of AQS in water as a function of concentration and pH; (2) laser photolysis of AQS in CH3CN and CH3CN/H20 mixtures, combined with emission spectroscopy; (3) steady-state photolytic study of the effect of AQS concentration and pH on the yield of photohydroxylation in water; (4) quenching of intermediates and inhibition of photohydroxylation by inorganic anions. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
103
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 3 publications
16
103
0
Order By: Relevance
“…Indeed, the evolution of AQ2S triplet state upon reaction with water produces transient adducts with water (where water is attached to either the aromatic ring or an oxygen atom), which either yield back ground-state AQ2S, or evolve into AQ2S-OH isomers (Maurino et al, 2008;Maddigapu et al, 2010;Bedini et al, in press). To support this, we observed the formation of a broad absorption band in the 350-550 nm range (that is, right in the range of EEM excitation wavelengths), which is fully compatible with the occurrence of α and β-hydroxy-AQ2S (Loeff et al, 1983; see also Figure SM1). …”
Section: Laser Flash Photolysis Measuressupporting
confidence: 57%
“…Indeed, the evolution of AQ2S triplet state upon reaction with water produces transient adducts with water (where water is attached to either the aromatic ring or an oxygen atom), which either yield back ground-state AQ2S, or evolve into AQ2S-OH isomers (Maurino et al, 2008;Maddigapu et al, 2010;Bedini et al, in press). To support this, we observed the formation of a broad absorption band in the 350-550 nm range (that is, right in the range of EEM excitation wavelengths), which is fully compatible with the occurrence of α and β-hydroxy-AQ2S (Loeff et al, 1983; see also Figure SM1). …”
Section: Laser Flash Photolysis Measuressupporting
confidence: 57%
“…The initial transformation rate of FFA under the adopted conditions was Rate FFA = (1.26±0.06)⋅10 (Loeff et al, 1983;Maurino et al, 2008, Maddigapu et al, 2010c. at pH 2 and (1.59±0.04)⋅10 2 [IBP] at pH 8.…”
Section: Reaction With Comentioning
confidence: 99%
“…It has a formation quantum yield Φ 3AQ2S* = 0.18 and a deactivation rate constant k 3AQ2S* = 1.1⋅10 7 s −1 (Loeff et al, 1983). The formation rate of 3 AQ2S* would be R 3AQ2S* = Φ 3AQ2S* P a…”
Section: Reaction With Comentioning
confidence: 99%
“…[61] Photohydroxylation is suppressed by the addition of halide ions. [37,59,62,63] As short-lived intermediates CT-complexes have been suggested that can either decay to the ground state or, at elevated halide concentrations, form dihalide radical anions and a semiquinone radical anion, QC À . [62] Oxidation of carbonate to CO 3 C À has also been reported.…”
mentioning
confidence: 99%